Beyond Illustration : The Art of Playboy. - Paul, Arthur (Chicago : Playboy Magazine, 1971)
Baum, Don ; Bouras, Harry ; Brown, Roger ; Burford, Byron ; Condak, Cliff ; Dali, Salvador ; Davidson, Herb ; Paul, Davis ; Gallo, Frank ; Ginzel, Rolnd ; Gudvanopoulos, Paul ; Gnoli, Domenico ; Van Hoeydonck, Paul ; Hoffman, Martin ; Holbrook, Peter ; Johnson, Ben ; Kohn, Misch ; Lanyon, Ellen ; Leslie, Alfred ; Neiman, Leroy ; Packard, Dave ; Parker, Robert Andrew ; Paschke, Ed ; Paul, Arthur ; Plumeri, James ; Pope, Kerig ; Punchatz, Don ; Renaud, Phill ; Rivers, Larry ; Rosenquist, James ; Rosofsky, Seumour ; Schackenberg, Roy ; Segal, George ; Strobel, Tom ; Suyeoka, George ; Ungerer, Tomi ; Utterback ; Bill ; Von Neumann, Robert ; Warhol, Andy ; Wesselman, Tom ; Weaver, Robert ; Wilcox, David ; Wirsum, Karl
Beyond Illustration : The Art of Playboy, rondreizende tentoonstelling in Noord-Amerika, Europa en Japan van 1971 tot 1974, Museum of Contemporary Art, Chicago, 1971, Antwerpen, 1972, etc.
boek